How sociable? An exploratory study of university brand visibility in social media - E. Botha; M. Farshid; L. Pitt (South African Journal of Business Management, 2011)
Social media has changed both the way in which organizations and their brands interact with their customers and the way in which business gets done. Brands are attempting to utilize social media to reach existing customers, gain new ones and build or maintain credibility and reputation. More importantly, brands need to measure their visibility in the most popular social media relative to that of competitors. This study describes a tool for collecting brand visibility information by looking at the visibility of various South African university brands and their relative positioning from a social media perspective. Correspondence analysis is then used to portray the various university brands in a multi-dimensional space so that they can be contrasted with each other in terms of their visibility in social media. The findings indicate that South African university brands are not distinctly positioned in social media and that none of them seems to currently have a concerted strategy for engaging its stakeholders in a particular social media. This means that there are both opportunities for those who manage these brands, and also threats to these institutions for taking a laissez fair attitude to social media in these times when social media are coming to dominate the Internet in particular and media in general.
Keywords: 650